FRI0312 Relationship Between Synovial Inflammation and Ultrasound Urate Deposits in Patients with Gout. (9th June 2015) - Perez-Ruiz, F.; Garmendia, E.; Urionagüena, I.; Chinchilla, S.P.
Abstract : Background: Urate intra-articular deposits are seen in ultrasound as double contour sign (DCS), hyperechogenic aggregates and tophi, but their separate contribution to synovial inflammation has yet to be determined. Objectives: To evaluate the association between DCS and tophi with the presence of synovial inflammation in ultrasound examination. Methods: Patients with crystal-proven gout were to be consecutively included, and had to be asymptomatic for at least 4 years (free of episodes of acute inflammation). They were recruited from two cohorts of prospective follow-up, one on active treatment and the other after withdrawal of urate-lowering therapy. Ultrasound of the 1st metatarsophalangeal joint (1st MTP) and of the non-dominant knee was performed by an explorer who was blinded for clinical data. The DCS was described as absent or present in less or more than 50% of the synovial surface. On the knee, the DCS location was registered as present in one or both femoral condyles. The presence of tophi was evaluated as hyperechogenic aggregates of at least 5mm maximum diameter, with a hypoechogenic halo associated. Synovial inflammation was evaluated by the measurement of synovial thickening with a semi-quantitative scale (0-3) and Power-Doppler (PD) semi-quantitative scale (0-3). Bi-variable and multiple regression analysis were made. Results: Ultrasound evaluation was proposed to 100 consecutive patients who fulfilled criteria, none on colchicine, NSAID or corticosteroid; of which 88 agreed to participate or attended the appointment. All of them were male, with a median age of 57±9 years, 74% with previous involvement of 1st MTP joint and 59% of the examined knee. Thirteen patients were excluded from analysis due to the presence of ultrasonographic chondrocalcinosis in the knee. The frequency of deposits in both cohorts was not different, thus a pooled analysis was conducted. The descriptive findings are presented in the table: Multiple regression analysis showed that the presence of synovitis >0 was only statistically associated in the 1st MTP to tophi (R 2 0.31), and in the knee to the presence of extense or bilateral DCS and tophi (R 2 0.28). The PD>0 signal was only associated in both 1st MTP and in knee to tophi (R 2 0.25 and 0.18). The more restrictive analysis of synovitis>1 and PD>1 did not show changes in the results. Conclusions: Ultrasonographic urate deposits are associated to synovitis or active synovitis (intra-articular synovitis with PD signal) as markers of synovial inflammation. The presence of tophi is the main factor associated, so the resolution of the intra-articular tophi seems to be the principal therapeutic goal. Acknowledgements: The study was funded by Asociacion de Reumatologos del Hospital de Cruces. Disclosure of Interest: None declared